Assessment of Limulus Test for Detecting Endotoxaemia. Issue 5917 (1st June 1974) - Fossard, D. P.; Kakkar, V. V.; Elsey, Penelope A.
Abstract : The occurrence of endotoxaemia in 46 surgical patients has been investigated using a sensitive preparation of limulus lysate. Altogether 23 patients with local and systemic Gram-negative infections were shown to have endotoxaemia. An overt infection is not a prerequisite for a positive limulus test result, since endotoxin can be absorbed via the peritoneal cavity in patients with "chemical" peritonitis. Over 70% of the tests performed during episodes of Gram-negative infection or peritonitis gave positive results. In 23 patients without clinical evidence of infection or peritonitis only 15% of the limulus test results were positive. The implications of these findings and the use of the test in clinical practice are discussed.